Toward A Theory of Optimal Financial Structure - Lin, Justin Yifu (The World Bank, 2009)
Each institutional arrangement in a financial system has both advantages and disadvantages in mobilizing savings, allocating capital, diversifying risks, and processing information when facilitating financial transactions. Meanwhile, the factor endowment in an economy at each stage of its development determines the optimal industrial structure in the real sector, which in turn constitutes the main determinant of the size distribution and risk features of viable enterprises with implications for the appropriate institutional arrangement of financial services at that stage. Therefore, there is an endogenously determined optimal financial structure for the economy at each stage of development